Overview of Garbage Management Plan On The MT B Star - Noor Sulistiyono; Bambang Setiawan; Fahreza Kautsar Setyarso (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
On the MT B Star ship, there are still some crew members who are caught dumping garbage in the ocean, this is very unfortunate because it can pollute the sea. Even though there have been provided trash cans according to the type of waste that exists. After further review, there are several factors that cause this to happen. The first factor is the lack of knowledge about MARPOL Annex v regulations by the crew. They seem to ignore the existing rules. The next factor is the small size of the trash can on the MT B Star ship. This causes the existing garbage to fill up very quickly. The solution that the author can convey is counseling the crew about the existing regulations and the importance of not throwing garbage in the sea. For the second factor, the company must provide a bigger trash can.